2021
DOI: 10.1002/sce.21625
|View full text |Cite
|
Sign up to set email alerts
|

The Awe is In the Process”: The nature and impact of professional scientists' experiences of awe

Abstract: In recent years, there has been a call in the research for greater attention to the role of affect in science learning and practice. Awe, which is characterized in the literature as an emotion that facilitates learning and motivates an orientation toward something larger than the self, appears frequently in scientists' descriptions of their work. Empirical evidence also suggests that awe has a unique relationship with scientific reasoning. However, this evidence comes primarily from tightly controlled laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…This perspective shift is related to awe promoting curiosity and being described as an epistemic emotion; experiencing awe can both reveal gaps in knowledge and promote learning (Gottlieb et al, 2018;Krogh-Jespersen et al, 2020;McPhetres, 2019;Cuzzolino, 2021): "[A] 5-day project that makes you realize that there is much more to this world and this universe than you could possibly imagine. "…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This perspective shift is related to awe promoting curiosity and being described as an epistemic emotion; experiencing awe can both reveal gaps in knowledge and promote learning (Gottlieb et al, 2018;Krogh-Jespersen et al, 2020;McPhetres, 2019;Cuzzolino, 2021): "[A] 5-day project that makes you realize that there is much more to this world and this universe than you could possibly imagine. "…”
Section: Resultsmentioning
confidence: 99%
“…These include nature, space, music and the arts, spiritual experiences, connectedness, and both one's own accomplishments and those of others (Graziosi & Yaden, 2019;Shiota et al, 2007;Sturm et al, 2020;. Moreover, direct experience on the part of the initiator is not required, as awe has been shown to be evoked through pictures, video, virtual and augmented reality, and narratives (Bai et al, 2017;Chen & Mongrain, 2020;Chirico et al, 2016;Chirico et al, 2017;Cuzzolino, 2021;Krenzer et al, 1018;Piff et al, 2015;Stellar et al, 2018;Rudd et al, 2012;Thompson, 2022a;Walker & Gilovich, 2020).…”
Section: Awe Explainedmentioning
confidence: 99%
See 1 more Smart Citation
“…The KPSI consists of a self-report on ten emotions: nine of them (rejection, concentration, insecurity, interest, boredom, confidence, satisfaction, dissatisfaction, and bashfulness) were in a previously validated questionnaire (Jimenez-Liso et al, 2019). We also included another emotion (surprise) because surprising observations could later elicit the "aha" or awe moment, which scientists have linked to the learning process and to situations of discovery (Cuzzolino, 2021). PSTs were able to select the emotion label related to all the key moments following the sequential order of the model-inquiry sequence.…”
Section: Instrument For Evaluating Pre-service Teachers Engagementmentioning
confidence: 99%
“…Research has shown that this type of reflective practice can be effective in enhancing the wellbeing of the individual ( East et al, 2010 ; Piff et al, 2015 ; Shiota et al, 2017 ). Moreover, eliciting awe can occur not only through sharing one’s own experiences, but also through learning about the experiences of others ( Rudd et al, 2012 ; Piff et al, 2015 ; Cuzzolino, 2021 ), including when hearing about the success stories of others ( Walker and Gilovich, 2021 ).…”
Section: Introductionmentioning
confidence: 99%